(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Nonlinear Painlevé equations play a pivotal role in various branches of mathematical physics, integrable systems, and applied mathematics,These equations, characterized by their complex and highly nonlinear nature, present significant challenges for analytical and numerical investigation. In this paper, we develop and present both analytical and numerical solutions for specific classes of nonlinear Painlevé equations. The analytical approach employs transformation techniques, perturbative expansions, and exact solution methods where applicable, while the numerical solutions are obtained using robust algorithms such as finite difference schemes, spectral methods, and iterative solvers. We validate the numerical results by comparing them with known analytical solutions and explore their accuracy, stability, and convergence properties. Furthermore, we discuss the implications of these solutions in physical models and highlight the intricate structures exhibited by the solutions, such as pole dynamics and asymptotic behaviors. This work contributes to the broader understanding of Painlevé equations and provides a framework for tackling similar nonlinear differential equations in applied contexts.